2016
DOI: 10.1111/icad.12158
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term changes in communities of native coccinellids: population fluctuations and the effect of competition from an invasive non‐native species

Abstract: Abstract. 1. We assessed the changes in abundance and community composition of native species of coccinellids (Coleoptera: Coccinellidae) on deciduous trees that occurred between 1970s and 2010s, in the Czech Republic.2. As the composition of adult communities varies with host plant and season, coccinellids were sampled in May-June from Acer, Betula and Tilia trees using a standardised sweeping method. This was done before (1976)(1977)(1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985)(1986)) and after (2011)(201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 35 publications
4
46
1
Order By: Relevance
“…Coccinellid communities usually consist of a few dominant and several less common and even rare species. Some communities, including those in agricultural crops, are species poor, although abundant in terms of the number of individuals (Honek et al, 2016). Changes in coccinellid communities in rice ecosystem are due to agricultural practice, habitat deterioration, invasion of non-native species and climate change (Honek et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Coccinellid communities usually consist of a few dominant and several less common and even rare species. Some communities, including those in agricultural crops, are species poor, although abundant in terms of the number of individuals (Honek et al, 2016). Changes in coccinellid communities in rice ecosystem are due to agricultural practice, habitat deterioration, invasion of non-native species and climate change (Honek et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…There are very few published long‐term studies of ladybird communities in Europe, and even fewer that have encompassed the early invasion phase of a non‐native species (but see Honěk et al ., , ). Our study shows a clear change in the ladybird community on lime trees over an 11‐year period in which H. axyridis invaded England, with an association between ladybird native status ( H. axyridis or native) and year (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Honek et al (2016), using datasets extending over 39 years, have shown that A. bipunctata was already declining in Europe before the arrival of H. axyridis. It is tempting to suggest that this decline might have occurred because of decreasing air pollution or other anthropogenic effects, leading to lower aphid populations generally.…”
Section: Datementioning
confidence: 99%